Implementasi Model Apersepsi dalam Pembelajaran Al-Qur’an Hadis pada Siswa Madrasah Tsanawaiyah al-Islamiyah Tonjong Bogor: Implementation of the Apperception Model in Learning Al-Qur'an Hadith Among Students of Madrasah Tsanawaiyah al-Islamiyah Tonjong Bogor - Abdul Jabar Idharuddin; Samsuddin, Samsuddin; Rahman, Rahman (Litera Academica Publishing, 2024)
This research aims to determine the implementation of the apperception model in learning Al-Qur'an Hadith for MTs Al-Islamiyah students to increase learning motivation. This research method uses qualitative methods with data collection techniques through observation, interviews and documentation. Data analysis took the form of descriptive interpretive and data validation using triagulation. The research results show that the implementation of the apperception model in learning is well realized, which is applied to aspects of planning, implementation and evaluation of learning accompanied by paying attention to supporting and inhibiting factors, as well as solutions to increase learning motivation. This research has implications for the importance of the teacher's role in implementing an apperception model in each lesson so that students are able to master old material and are ready to follow new learning material.